The association between statin use and diabetic nephropathy in US adults: data from NHANES 2005 - 2018 - Guo, Jinjing; Jiang, Zhibing; Xia, Yiping; Wang, Hui; Tang, Qun; Meng, Bin (Frontiers in Endocrinology, 2024)
Background: A serious consequence of diabetes is diabetic nephropathy (DN), which is commonly treated by statins. Studies evaluating the effects of statin medication have yielded inconsistent results regarding the potential association with diabetic nephropathy. To manage diabetic nephropathy's onset and improve the quality of life of patients, it is imperative to gain a comprehensive understanding of its contributing factors.Data and Methods: Our study was conducted using the National Health and Nutrition Examination Survey (NHANES) as well as weighted multivariate logistic regression models to determine the odds ratio (OR) and 95% confidence intervals (95%CI) for diabetic nephropathy. We conducted stratified analyses to examine the impact of statins and the duration of their usage on diabetic nephropathy in different subgroups. A nomogram model and the receiver operating characteristic (ROC) curve were also developed to predict DN risk.Results: Statin use significantly increased the incidence of DN (OR=1.405, 95%CI (1.199,1.647), p<0.001). Individuals who used statins for 5 to 7 years were more likely to develop diabetic nephropathy (OR=1.472, 95%CI (1.057,2.048), p=0.022) compared to those who used statins for 1-3 years (OR=1.334, 95%CI (1.058,1.682), p=0.015) or <1 year (OR=1.266, 95%CI (1.054,1.522), p = 0.012). Simvastatin has a greater incidence of diabetic nephropathy (OR=1.448, 95%CI(1.177, 1.78), P < 0.001).Conclusions: Taking statins long-term increases the risk of DN. Statin use is associated with an increased risk of DN. Caution should be exercised when prescribing atorvastatin and simvastatin for long-term statin therapy.